Design emocional para melhora da autoestima e bem-estar: o aumento da autoestima e do bem-estar das mulheres através do incentivo da rotina de autocuidado - Hörlle, Ana Carolina Agostini (Universidade do Vale do Rio dos Sinos, 2021)
The pandemic period brought about several changes in the lives and routine of individuals around the world. Scientific researches carried out in 2020 indicate that depression, anxiety, feelings of sadness and nervousness were more present in the lives of Brazilians, and it is possible to perceive the influence of the pandemic context on the well-being and self-esteem of the population in general. In view of this, the present study intended, through tools and methodologies of strategic design, with a focus on emotional design and design for experience, to develop a project, at the conclusion of the course, that stimulates the self-esteem of women between 16 and 35 years old, causing improves their well-being. From these perspectives, the “Confié Skincare” product-service system was developed, which proposes the practice of self care through skincare, in order to promote a moment of pleasure and well-being to the target audience. The system is made up of customizable dermocosmetic products, promoting the tangibility of the system; by website, providing information about the products; and by profiles on social networks Instagram, TikTok and Pinterest, aiming to create connection and interaction with members of the public individually in each of the networks. All these elements are autonomous, but related, creating synergies to encourage women to practice self-care, promoting increased self-esteem and improved well-being.
Keywords: Design emocional; Autoestima; Bem-estar; Autocuidado; Skincare; Emotional design; Self-esteem; Well-being; Self-care